Nickel as a potential disruptor of thyroid function: benchmark modelling of human data - Maric, Djurdjica; Baralic, Katarina; Javorac, Dragana; Mandic-Rajcevic, Stefan; Zarkovic, Milos; Antonijevic, Biljana; Djukic-Cosic, Danijela; Bulat, Zorica; Djordjevic, Aleksandra Buha (Frontiers in Endocrinology, 2023)
Nickel (Ni) is one of the well-known toxic metals found in the environment. However, its influence on thyroid function is not explored enough. Hence, the aim of this study was to analyse the potential of Ni to disrupt thyroid function by exploring the relationship between blood Ni concentration and serum hormone levels (TSH, T4, T3, fT4 and fT3), as well as the parameters of thyroid homeostasis (SPINA-GT and SPINA-GD) by using correlation analysis and Benchmark (BMD) concept. Ni concentration was measured by ICP-MS method, while CLIA was used for serum hormone determination. SPINA Thyr software was used to calculate SPINA-GT and SPINA-GD parameters. BMD analysis was performed by PROAST software (70.1). The limitations of this study are the small sample size and the uneven distribution of healthy and unhealthy subjects, limited confounding factors, as well as the age of the subjects that could have influenced the obtained results. The highest median value for blood Ni concentration was observed for the male population and amounted 8,278 µg/L. Accordingly, the statistically significant correlation was observed only in the male population, for Ni-fT4 and Ni-SPINA-GT pairs. The existence of a dose-response relationship was established between Ni and all the measured parameters of thyroid functions in entire population and in both sexes. However, the narrowest BMD intervals were obtained only in men, for Ni - SPINA-GT pair (1.36-60.9 µg/L) and Ni - fT3 pair (0.397-66.8 µg/L), indicating that even 78.68 and 83.25% of men in our study might be in 10% higher risk of Ni-induced SPINA-GT and fT3 alterations, respectively. Due to the relationship established between Ni and the SPINA-GT parameter, it can be concluded that Ni has an influence on the secretory function of the thyroid gland in men. Although the further research is required, these findings suggest possible role of Ni in thyroid function disturbances.